The role of modern communication methods in enhancing the economic value of heritage in the post-covid-19 era - Kosmas, Petros C.; Vatikiotis, Leonidas; Andreev, Hristo (My University, 2023)
The relationship between cultural heritage, economic value, and modern communication methods is recognized as being of great interest due to the specialization that has occurred and the originality that it possesses. Prior to a few years ago, it would probably have been impossible to conduct this type of discussion. Since then, accumulated knowledge as well as unanswered questions and the evolution of interdisciplinarity have formed the basis for proposing methods, frameworks, and responses that to one degree or another deepen and advance collective knowledge in this interdisciplinary area. The approach taken in this chapter demonstrates its originality, since it attempts to integrate different disciplines, such as cultural heritage, economic value, and modern communication methods. As a result of this chapter, it is possible to determine on a certain level the degree of difficulty of the proposed approach.
Keywords: communication; communication methods; economic value; covid-19